State-dependent memory mechanisms insights from neural circuits and clinical implications - Liu, Yang; Zhang, Guohui; Qi, Rui; Ma, Jie; Xu, Jianguang (Frontiers in Cellular Neuroscience, 2025)
State dependent memory (SDM) occurs when memory retrieval varies with the individual's psychological and physiological state at encoding and recall. Growing evidence shows that internal states shape memory performance across all phases of memory. Examples include affective and physiological conditions, medication effects, and disease states. This review examines how these states affect encoding, storage, and retrieval. We argue that internal states modulate activity in brain regions involved in memory by altering neurotransmitter signaling and by inducing plastic organization of neural circuits and networks. We believe this perspective can guide personalized electrical neuromodulation and multimodal intervention strategies for memory disorders.